2013
DOI: 10.5057/ijae.12.375
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Sensory Properties of Textures that Appeal to Human Touch

Abstract: Some textures and materials are appealing to our sense of touch in daily life. What makes us intuitively feel like touching these particular things? Haptic invitations of such materials have rarely been investigated. The present report identifies the relationships between the visual and sensory properties of textures and their haptic invitations. We used 24 artificial clay textures that were varied along four visual factors, and quantified the degrees of haptic invitations of these textures using a ranking app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Nagano et al [4], [5], [6] revealed that linear combinations of the visual properties of materials described degrees of haptic invitation with a degree of accuracy ranging 70-80 percent. They found that although glossiness and surface shapes strongly affect haptic invitation, surface colors hardly affect it at all.…”
Section: Introductionmentioning
confidence: 98%
“…Nagano et al [4], [5], [6] revealed that linear combinations of the visual properties of materials described degrees of haptic invitation with a degree of accuracy ranging 70-80 percent. They found that although glossiness and surface shapes strongly affect haptic invitation, surface colors hardly affect it at all.…”
Section: Introductionmentioning
confidence: 98%
“…Impression is affected by many factors, including nationality [9,10], motifs of paintings [11], visual and sensory properties of textures [12], calligraphic styles [13], personality [14], and mood [15,16]. However, to the best of our knowledge, no study has yet examined the effect of seasons on an impression.…”
Section: Introductionmentioning
confidence: 94%
“…Potential impression factors are often obtained from experimental results through the application of factor analysis [1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In their investigation into the effects of seasons on potential impression factors [18], Tamai et al applied factor analysis separately to the scores of females and males because there were significant differences between them and obtained the following four factors: Evaluation, Potency, Sharpness, and Freshness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Nagano, Okamoto, and Yamada [12] determined the relationship between the visual and sensory properties of the texture and its tactile invitations through the texture study of artificial clay. The result showed that texture-related visual and sensory factors were useful for designing attractive textures.…”
Section: Related Studiesmentioning
confidence: 99%